Minimizing Risks and Maximizing Benefits: Risk Management Strategies in Productive Waqf Management - Qurrotul A’yuni (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
This study aims to examine marketing management strategies that can be applied by educational institutions to enhance their competitiveness in the digital era. In an era increasingly influenced by technological advancements, digital marketing is crucial for educational institutions to attract prospective students and improve their reputation. This research employs a literature review method by analyzing various relevant sources on digital marketing, marketing management strategies, and the competitiveness of educational institutions. The findings reveal that implementing digital marketing strategies, such as the use of social media, content marketing, and search engine optimization (SEO), can enhance the competitiveness of educational institutions in an increasingly competitive market. Understanding productive waqf Waqf is an important concept in the Islamic economic system that has been known since the time of the Prophet Muhammad SAW. As a social and religious instrument, waqf has great potential to empower people and help solve various social problems. Waqf is generally considered as property that is donated permanently, which is used for social purposes such as education, health and infrastructure development. ). Productive waqf includes several components, including identifying, controlling, implementing Good Corporate Governance, monitoring and evaluation systems. Risk identification in productive waqf investments is an important step to ensure the continuity and effectiveness of waqf asset management. Risk disclosure strategy in productive waqf management Minimizing Risk and Maximizing Profits in Productive Waqf Management Productive waqf management requires an effective management strategy to ensure waqf assets can provide sustainable benefits, ). Productive waqf includes several components, including identifying, controlling, implementing Good Corporate Governance, monitoring and evaluation systems. Risk identification in productive waqf investments is an important step to ensure the continuity and effectiveness of waqf asset management. Risk disclosure strategies in productive waqf management Minimizing risks and maximizing profits in productive waqf management Productive waqf management requires effective management strategies to ensure waqf assets can provide sustainable benefits Keywords: Marketing Management, Educational Institutions, Digital Era Meminimalkan Risiko dan Maksimalkan Keuntungan Strategi Manajemen Risiko dalam Pengelolaan Wakaf Produktif Qurrotul A’yuni STAI An Najah Indonesia Mandiri Sidoarjo qurrotulyuni27@gmail.com ABSTRAK Pengertian wakaf produktif Wakaf merupakan salah satu konsep penting dalam sistem ekonomi Islam yang telah dikenal sejak zaman Nabi Muhammad SAW. Sebagai instrumen sosial dan keagamaan, wakaf memiliki potensi besar untuk memberdayakan umat dan membantu memecahkan berbagai masalah sosial. Wakaf pada umumnya dianggap sebagai harta yang disedekahkan secara permanen, yang digunakan untuk kepentingan sosial seperti pendidikan, kesehatan, dan pembangunan infrastruktur. ). wakaf produktif mencakup beberapa komponen, diantaranya mengindentifikasi, mengendalikan, penerapan Good Corporate Governance, sistem monitoring dan evaluasi. Risiko identifikasi dalam investasi wakaf produktif merupakan langkah penting untuk memastikan kelangsungan dan efektivitas pengelolaan aset wakaf. Strategi pengungkapan risiko dalam pengelolaan wakaf produktif Meminimalkan Risiko dan Memaksimalkan Keuntungan dalam Pengelolaan Wakaf Produktif Pengelolaan wakaf produktif memerlukan strategi manajemen yang efektif untuk memastikan aset wakaf dapat memberikan manfaat berkelanjutan, ). wakaf produktif mencakup beberapa komponen, diantaranya mengindentifikasi, mengendalikan, penerapan Good Corporate Governance, sistem monitoring dan evaluasi. Risiko identifikasi dalam investasi wakaf produktif merupakan langkah penting untuk memastikan kelangsungan dan efektivitas pengelolaan aset wakaf. Strategi pengungkapan risiko dalam pengelolaan wakaf produktif Meminimalkan Risiko dan Memaksimalkan Keuntungan dalam Pengelolaan Wakaf Produktif Pengelolaan wakaf produktif memerlukan strategi manajemen yang efektif untuk memastikan aset wakaf dapat memberikan manfaat berkelanjutan Kata Kunci : Manajemen Pemasaran, Lembaga Pendidikan, Era Digital